Effects of Fe concentration on the ion-irradiation induced defect evolution and hardening in Ni-Fe solid solution alloys. (December 2016) - Jin, Ke; Guo, Wei; Lu, Chenyang; Ullah, Mohammad W.; Zhang, Yanwen; Weber, William J.; Wang, Lumin; Poplawsky, Jonathan D.; Bei, Hongbin
Abstract: Understanding alloying effects on the irradiation response of structural materials is pivotal in nuclear engineering. To systematically explore the effects of Fe concentration on the irradiation-induced defect evolution and hardening in face-centered cubic Ni-Fe binary solid solution alloys, single crystalline Ni-xFe (x = 0–60 at%) alloys have been grown and irradiated with 1.5 MeV Ni ions. The irradiations have been performed over a wide range of fluences from 3 × 10 13 to 3 × 10 16  cm −2  at room temperature. Ion channeling technique has shown reduced damage accumulation with increasing Fe concentration in the low fluence regime, which is consistent to the results from molecular dynamic simulations. No irradiation-induced compositional segregation was observed in atom probe tomography within the detection limit, even in the samples irradiated with high fluence Ni ions. Transmission electron microscopy analyses have further demonstrated that the defect size significantly decreases with increasing Fe concentration, indicating a delay in defect evolution. Furthermore, irradiation induced hardening has been measured by nanoindentation tests. Ni and the Ni-Fe alloys have largely different initial hardness, but they all follow a similar trend for the increase of hardness as a function of irradiation fluence. Graphical abstract: Image 1